Figure S2 from T-cell Receptor Therapy Targeting Mutant Capicua Transcriptional Repressor in Experimental Gliomas - Michael Kilian (16697663) (2025)
Supplementary Figure 2: Molecular features of A2.DR1 MHC-humanized gliomas. A. Verification of the CRISPR-Cas9-mediated functional KO of p53 and Nf1 in the A2.DR1 glioma cell line. B. Copy number variations (CNVs) in the A2.DR1 glioma cell line. C. Chromosomal distribution of CNVs D. Representative immunofluorescence image of A2.DR1 glioma orthotopically injected into the brain of adult A2.DR1 mice, 20 days after injection. E. Relative expression of Cic in wild-type and CicR215W overexpressing A2.DR1 glioma cells as determined by RT-qPCR. F: Immunoblot depicting overexpression of the Cic protein in the CicR215W transfected cell line compared to the parental line (WT).